ANALYSIS OF HOTEL EMPLOYEES' UNDERSTANDING OF SIA USED IN DAILY OPERATIONS - Mursandi; Arifuddin; Syarifuddin (ZILLZELL MEDIA PRIMA, 2026)
This study aims to analyze the level of hotel employees' understanding of accounting information systems implemented in daily operations, identify factors influencing this understanding, and evaluate the contribution of employee understanding to system effectiveness. The research method used is a descriptive qualitative approach with data collection techniques through in-depth interviews with five informants from various hotel divisions. Data analysis uses the Miles and Huberman interactive model technique which includes data reduction, data presentation, and conclusion drawing. The research results show that the level of employee understanding varies based on length of service and job position, where managerial employees have a more comprehensive understanding compared to operational employees. Accounting information systems have been proven to increase operational efficiency and accuracy, produce higher quality data compared to manual systems, and support management decision-making. However, there are obstacles in the form of lack of integration between departments, limited technical training, and technology competency gaps. This research recommends the importance of continuous training programs, increased system integration, and consistent management support to optimize the effectiveness of accounting information systems in hotel operations.